Analyzing Computational Thinking Skills in Mathematics Education: Evidence from Eleventh Grade Students at SMA Negeri 3 Mataram - Ahmad Rizky Pratama; Dewi Lestari Putri; Muhammad Fajar Hidayat (Journal of Science and Mathematics Education, 2026)
Computational thinking has emerged as a fundamental competency in 21st-century education, particularly within mathematics learning, where problem-solving, abstraction, and algorithmic reasoning are essential. However, empirical evidence regarding students’ computational thinking skills in secondary education, especially in developing country contexts, remains limited. This study aims to analyze the level and characteristics of computational thinking skills among eleventh grade students at SMA Negeri 3 Mataram, Indonesia. A quantitative descriptive research design was employed, involving 120 students selected through stratified random sampling. Data were collected using a validated computational thinking test instrument encompassing four key dimensions: decomposition, pattern recognition, abstraction, and algorithmic thinking. The data were analyzed using descriptive statistics and inferential analysis to identify trends and variations in students’ performance. The findings reveal that students’ overall computational thinking skills are at a moderate level, with relatively higher achievement in pattern recognition and lower performance in abstraction and algorithmic thinking. Furthermore, differences in computational thinking skills were observed based on students’ academic achievement levels. These results highlight the need for integrating computational thinking-oriented instructional strategies in mathematics classrooms to enhance students’ higher-order thinking skills. The study contributes to the growing body of literature on computational thinking in mathematics education and provides practical implications for curriculum development and instructional design in similar educational contexts.